Characterization of a Population with Visual, Auditory, Speech and Motor Disabilities, for Their Linking to Undergraduate Programs at a University in Colombia - Luz Myrian Rojas-Rojas; Néstor Arboleda-Toro; Leidy Johanna Pinzón-Jaime (Revista Electrónica Educare)
This article presents the results of an unpublished research project whose objective was to characterize a population with visual, hearing, speech and motor disabilities. The research quantified potential users of the programs offered by the Faculty of Distance Education (FESAD) at the Pedagogical and Technological University of Colombia (UPTC). It had an exploratory-descriptive methodological design with random sampling. Surveys were applied to young high school students and adult bachelors by using Braille system and a digital sign language translator. For data analysis, a quantitative statistical method was implemented. The results showed that, from young bachelors, 53% were women, 51% adults were men; 57% of young people were between 18 and 21 years old, 47% of adults were between 22 and 30 years old, and 65% of adult bachelors did not work. From the preferred university careers to study, a 28% of young people preferred engineering; 21%, economic and administrative sciences; 15%, arts; and 13%, education sciences. 27% of adult bachelors preferred engineering; 18%, economic and administrative sciences; and 15%, education sciences. 85% of youth and 71% of adult bachelors were deaf. It is concluded that there is a vulnerable population with disabilities and with an obvious lack of opportunities to access higher education. FESAD has trained teachers in designing an integrated and inclusive curriculum for the development of labor skills. FESAD also has technical and technological resources to take care of this population. It is recommended to boost higher education policies for social inclusion in Colombia, and conduct new studies on causes and effects to design and implement programs that apply these policies.